LEARNING TRAJECTORY PEMBELAJARAN LUAS PERMUKAAN KUBUS DAN BALOK - Rani Refianti; Idul Adha (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2018)
Learning trajectory is the flow of students' thinking resulting from Hypothetical Learning Trajectory (HLT). Learning trajectory that is produced in learning material on the surface area of cubes and beams can be used as a basis for teachers in developing models, methods and teaching materials to be used in learning. The research method used in developing learning trajectories is a design research research method that aims to develop the local instruction theory through collaboration between researchers and teachers in improving the quality of learning. The design research method consists of three stages namely pre-experiment, teaching experiment and restropective analysis. Data collection techniques used in this study are documentation, interviews and observations, and tests. The data obtained were then analyzed descriptively. Analysis of data from documentation, interviews, observations, and tests were carried out qualitatively